Production function responses in post-partum Bos indicus (Zebu) cattle to nutrition supplementation - Mukasa-Mugerwa, E. (Swedish University of Agricultural Sciences, 1996)
Many efforts to increase milk and meat production by importing temperate breeds into the tropics are constrained by the breeds' lack of adaptation to tropical diseases, biologic and present management stresses. Moreover, feeding regimes developed for temperate breeds also do not suit animals indigenous to the tropics because of their multipurpose nature and different nutrient utilization strategies. Data are presented indicating that given adequate feeding, Zebu cows calving in this condition produced limited milk for calf growth, directing nutrients more towards repletion of body reserves. Animals calved in good condition attempt to produce as much milk as their genetic potential would allow. It is therefore plausible that the ability of Zebu cattle for fat deposition (an adaptation strategy) might be important and related to their milk yield potential. The need to investigate the possibility of using molecular biology techniques for increased accuracy in identifying indigenous animals that are better adapted to production and survival under tropical conditions is emphasized.